Pentingnya Penyelesaian Konflik Tanah Melalui Pembagian Warisan Yang Adil - Ella Putri Permatasari; Nur Fira Amalia Fabrianti; Qutrotu Salsabila; Muhammad Zalfa Roqiqo Abada (Concept: Journal of Social Humanities and Education, 2023)
As a manifestation of mutual respect and an attitude of living in harmony, it is important to resolve land conflicts through a fair distribution of inheritance. Equitable distribution of inheritance is a process of distributing assets and land rights proportionally according to the needs and contributions of each party involved. Equitable distribution will create social justice and reduce injustice that may occur, so as to reduce conflict, one of which is by means of mediation. Equitable distribution of inheritance can also help develop communities and increase economic well-being. Also intended to eliminate feelings of resentment due to disputes that arise. By means of mediation, it is hoped that this family spirit will be maintained so that a harmonious and peaceful life can be created.